Single-incision versus conventional laparoscopic appendectomy: A case-match study. (3rd March 2014) - Joliat, Gaëtan-Romain; Uldry, Emilie; Demartines, Nicolas; Schäfer, Markus
Background: Three-port laparoscopic appendectomy is considered standard in many countries for the surgical treatment of acute appendicitis. Single-incision laparoscopic technique has been recently introduced and is supposed to minimize the aggression induced by surgery. Regarding appendectomy, comparison with standard laparoscopy, benefits and drawbacks of this novel technique remain to be evaluated. The goal of this study was to assess single-incision laparoscopic appendectomy compared to conventional laparoscopic appendectomy in terms of operation time, length of hospital stay, complication rate, and postoperative antibiotherapy rate. Methods: From February 2011 to December 2011, single-incision laparoscopic appendectomy was proposed to patients admitted to the emergency room of the University Hospital of Lausanne (CHUV, Lausanne, Switzerland), diagnosed with uncomplicated acute appendicitis. Preoperative patients' information, technical difficulties during the operation, and postoperative follow-ups were recorded. Every patient who underwent single-incision laparoscopic appendectomy (n = 20) was matched 1:3 conventional laparoscopic appendectomy (n = 60), controlling for age, gender, body mass index, American Society of Anesthesiologists score, and histopathological findings. Results: No statistically significant differences for median operation time, length of hospital stay, complication rate, and need for postoperative antibiotherapy were found. In 5 out of 20 single-incision laparoscopic appendectomy patients the Endoloop ® Ligature was judged difficult to put in place. Conclusion: This study suggests that single-incision laparoscopic appendectomy is a feasible and effective operative technique for uncomplicated acute appendicitis.